MgO-based slag stopper castable for converter steelmaking and tapping

Through the combination of MgO-based castable and optimized binding agent, the problems of high-temperature strength and long manufacturing cycle caused by the increase in cement usage in the prior art are solved, and the high-temperature strength and short manufacturing cycle of the castable are realized, which reduces the manufacturing cost and Risk of damage.

CN119285333APending Publication Date: 2025-01-10HAIWEI ZHONGXING HIGH-GRADE MAGNESIA BRICK CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411421452.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When existing slag stopper castables are used under high-temperature steel outlet conditions, the increase in cement consumption leads to a decrease in the high-temperature strength, a long manufacturing cycle and easy to damage, affecting production efficiency and effect.

Method used

MgO-based castable is used, mainly composed of materials such as heavy-burned magnesium sand, goose-stone, slag powder, etc., and binders such as phenolic resin, epoxy resin, polyurethane resin, etc. are used to introduce cyclohexanone peroxide and cobalt cycloalkane acid. Accelerator, optimize the particle ratio and component ratio to improve the low-temperature and high-temperature strength and thermal shock performance of the castable.

Benefits of technology

Shorten the manufacturing cycle, improve the low and high temperature strength of the castable, enhance the thermal shock performance, reduce manufacturing costs, and reduce the risk of damage during mold release and transportation.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an MgO-based slag stopper castable for converter steelmaking and tapping, which comprises a castable aggregate and a binding agent, and the castable aggregate comprises the following components in parts by weight: 50-60 parts of dead burnt magnesia; 15 to 25 parts of goose warming stone; 8-15 parts of slag powder; 5-10 parts of coke powder; 5 to 10 parts of bentonite; the binding agent comprises the following components in parts by weight: 35-45 parts of phenolic resin; 15 to 25 parts of epoxy resin; 10 to 20 parts of polyurethane resin; 5 to 10 parts of polystyrene; 0-5 parts of organic silicon powder; 0-5 parts of diphenyl ether; 3-5 parts of sodium alginate; 2 to 5 parts of cyclohexanone peroxide; 1-5 parts of cobalt naphthenate; the weight percentage ratio of the castable aggregate to the binding agent is 100: (1.5-2.5). The novel castable has the beneficial effects that the novel castable which takes dead burnt magnesia as a main material and is added with a certain amount of goose warming stone as a weight increasing aggregate has the advantages of high low-temperature strength and high-temperature strength, good thermal shock resistance, short manufacturing period and the like, and the dead burnt magnesia, the goose warming stone material, the slag powder and other raw materials are easy to obtain and low in price; and therefore, the manufacturing cost of the slag stopping plug castable is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a MgO-based slag stopper castable for steelmaking and tapping in a converter. Background Art

[0002] The slag stopper is a refractory product with a gyroscope-like shape and a guide rod with a smaller diameter. The thick end of the gyroscope has 3 grooves and 6 edges, which can destroy the eddy current of molten steel and reduce the slag entrainment of the eddy current. It has the dual functions of slag stopping and eddy current suppression. It is one of the slag stopping tools commonly used in converter steelmaking and tapping.

[0003] Refractory aggregate is the main material in the organizational structure of refractory castables, which affects the physical and high-temperature performance of its products. At present, most of the existing slag plugs use high-aluminum castables with brown corundum and special-grade bauxite as refractory aggregates, and usually use cement as a binder. For this kind of refractory castable bound with cement, if the amount of cement is increased, the high-temperature strength of the castable will be reduced, affecting the performance, especially when the tapping temperature is high and the tapping conditions are poor. Therefore, it is generally necessary to add an appropriate amount of high-grade refractory powder or ultrafine powder, or improve the material of the overall castable to reduce the amount of cement to ensure the effectiveness of use. In other words, low-cement high-aluminum castables are generally used at present. However, low-cement castables are easily damaged due to the long in-mold curing time during the production process, demoulding and handling, and the low strength during installation and delivery, which affects the slag blocking effect and restricts normal production. Summary of the invention

[0004] In order to overcome the defects of the prior art, the technical problem solved by the present invention is to provide a MgO-based slag stopper castable for converter steelmaking and tapping, which is a new type of castable with heavy burned magnesia as the main material and a certain amount of goose warm stone as the weight-increasing aggregate. The castable has the advantages of high low-temperature strength and high-temperature strength, good thermal shock resistance, short manufacturing cycle, etc. Raw materials such as heavy burned magnesia, goose warm stone material, and slag powder are easily available and inexpensive, thereby greatly reducing the manufacturing cost of the slag stopper castable.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A MgO-based converter steelmaking slag plug castable material, comprising a castable aggregate and a binder, characterized in that the components of the castable aggregate are calculated by weight:

[0007] 50-60 parts of dead-burned magnesia; 15-25 parts of goose warm stone; 8-15 parts of slag powder; 5-10 parts of coke powder; 5-10 parts of bentonite;

[0008] The components of the binder are calculated by weight:

[0009] 35-45 parts of phenolic resin; 15-25 parts of epoxy resin; 10-20 parts of polyurethane resin; 5-10 parts of polystyrene; 0-5 parts of organosilicon powder; 0-5 parts of diphenyl ether; 3-5 parts of sodium alginate; 2-5 parts of cyclohexanone peroxide; 1-5 parts of cobalt naphthenate;

[0010] The weight percentage of the castable aggregate to the binder is 100:1.5-2.5.

[0011] Preferably, the components of the castable aggregate are calculated by weight:

[0012] 55 parts of dead-burned magnesia; 20 parts of goose warm stone; 10 parts of slag powder; 7.5 parts of coke powder; 7.5 parts of bentonite;

[0013] Preferably, the components of the binder are calculated by weight:

[0014] 40 parts of phenolic resin; 20 parts of epoxy resin; 15 parts of polyurethane resin; 7.5 parts of polystyrene; 3.5 parts of silicone powder; 3.5 parts of diphenyl ether; 4 parts of sodium alginate; 4 parts of cyclohexanone peroxide; 2.5 parts of cobalt naphthenate;

[0015] Preferably, the weight percentage of the castable aggregate to the binder is 100:2.

[0016] Furthermore, the ratio of the particles of the dead-burned magnesia is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=2:2:1.

[0017] Furthermore, the ratio of the particles of the goose-warming stone is: 3mm<particle size≤5mm: 1mm<particle size≤3mm: particle size<1mm=2:1:1.

[0018] Furthermore, the ratio of the particles of the slag powder is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=1:1.5:1.

[0019] Furthermore, the dead-burned magnesia has a MgO content greater than or equal to 97%, a CaO / SiO2 ratio not less than 2, and a bulk density not less than 3.34 g / cm 3 , magnesia with a porosity of no more than 3% and well-developed grain boundaries.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The slag plug castable of the present invention uses a phenolic resin, an epoxy resin, and a polyurethane resin as a binder, and introduces a cyclohexanone peroxide curing agent and a cobalt naphthenate accelerator for use in combination, so that the demoulding and curing time of the slag plug is greatly shortened, the demoulding curing period is 15 to 25 minutes, and the curing period after demoulding is 1.5 to 3.5 hours, thereby shortening the manufacturing cycle;

[0022] 2) The slag plug castable of the present invention has polystyrene, silicone powder, diphenyl ether and sodium alginate introduced into its binder for modification, which can greatly improve the low-temperature strength and high-temperature strength of the overall slag plug, improve the thermal shock resistance, and overcome the phenomenon of easy damage due to low strength during demoulding, transportation, installation and delivery;

[0023] 3) The slag plug castable of the present invention has an aggregate main component of dead-burned magnesia and a bulk density of not less than 3.34 g / cm 3 , compared with other bauxite (bulk density 2.2 ~ 2.6g / cm 3 ) as the main component of the castable, it has a higher strength advantage;

[0024] 4) The southern part of Liaoning Province has high-quality dolomite resources that are rare in the world. It has the characteristics of large reserves, high grade, shallow burial and easy mining. The reserves are about 3.4 billion tons, accounting for roughly 85% of the national reserves and 20% of the world's reserves. In addition, raw materials such as goose warm stone and slag powder are easy to obtain and cheap, which greatly reduces the manufacturing cost of slag plug castables. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be further clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] [Example 1]:

[0027] A MgO-based slag stopper castable for steelmaking and tapping in a converter comprises a castable aggregate and a binder. The components of the castable aggregate are as follows by weight:

[0028] 55 parts of dead-burned magnesia; 20 parts of goose warm stone; 10 parts of slag powder; 7.5 parts of coke powder; 7.5 parts of bentonite;

[0029] The components of the binder are calculated by weight:

[0030] 40 parts of phenolic resin; 20 parts of epoxy resin; 15 parts of polyurethane resin; 7.5 parts of polystyrene; 3.5 parts of silicone powder; 3.5 parts of diphenyl ether; 4 parts of sodium alginate; 4 parts of cyclohexanone peroxide; 2.5 parts of cobalt naphthenate;

[0031] The weight percentage of the castable aggregate to the binder is 100:2.

[0032] The method for preparing a MgO-based slag stopper castable for steelmaking and tapping in a converter of the present embodiment comprises the following specific steps:

[0033] 1) Preparation of castable aggregate:

[0034] Weigh 55 kg of dead-burned magnesia; 20 kg of goose warm stone; 10 kg of slag powder; 7.5 kg of coke powder; and 7.5 kg of bentonite by weight, wherein the ratio of the particles of the dead-burned magnesia is: 3 mm < particle size ≤ 5 mm: 1 mm < particle size ≤ 3 mm: particle size < 1 mm = 2:2:1;

[0035] The ratio of the particles of the goose warm stone is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=2:1:1;

[0036] The ratio of the slag powder particles is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=1:1.5:1;

[0037] The particle size of the coke powder is 400 mesh;

[0038] The particle size of the bentonite is 800 mesh;

[0039] The above materials were mixed and stirred for 15 minutes to obtain 100 kg of castable aggregate.

[0040] In this embodiment, the dead-burned magnesia is a dead-burned magnesia product produced by Haicheng Lier Magxita Materials Co., Ltd., whose MgO content is greater than or equal to 97%, CaO / SiO2 is not less than 2, and the bulk density is not less than 3.34 g / cm 3 , the porosity is no more than 3% and the grain boundaries are well developed.

[0041] 2) Preparation of binder

[0042] The preparation of the binder comprises the following steps:

[0043] Step 1: Weigh 0.80Kg of phenolic resin, 0.40Kg of epoxy resin, 0.30Kg of polyurethane resin, 0.15Kg of polystyrene, 0.07Kg of silicone powder, 0.07Kg of diphenyl ether, and 0.08Kg of sodium alginate according to weight, pour into a stirring tank and mix and stir for 5 minutes at room temperature.

[0044] Step 2: Weigh 0.05 kg of cobalt naphthenate, pour it into a stirring tank and mix and stir for 8 minutes at room temperature;

[0045] Step 2: Finally, weigh 0.08 kg of cyclohexanone peroxide, pour it into a stirring tank, mix and stir at room temperature for 15 minutes to obtain 2 kg of binder.

[0046] 3) Preparation of castables:

[0047] Pour 2 kg of the binder prepared in step 2) into 100 kg of castable aggregate prepared in step 1), that is, the ratio of castable aggregate to binder is 100:2, and mix and stir for 30 minutes to obtain the castable.

[0048] [Example 2]:

[0049] A MgO-based converter steelmaking slag plug castable for tapping, comprising a castable aggregate and a binder, wherein the components of the castable aggregate are as follows by weight:

[0050] 50 parts of dead-burned magnesia; 22.5 parts of goose warm stone; 12.5 parts of slag powder; 5.5 parts of coke powder; 9.5 parts of bentonite;

[0051] The components of the binder are calculated by weight:

[0052] 35 parts of phenolic resin; 22.5 parts of epoxy resin; 17.5 parts of polyurethane resin; 6.5 parts of polystyrene; 4.5 parts of organosilicon powder; 4.5 parts of diphenyl ether; 4.5 parts of sodium alginate; 3.0 parts of cyclohexanone peroxide; 2.0 parts of cobalt naphthenate;

[0053] The weight percentage of the castable aggregate to the binder is 100:1.5.

[0054] The method for preparing a MgO-based slag stopper castable for steelmaking and tapping in a converter of the present embodiment comprises the following specific steps:

[0055] 1) Preparation of castable aggregate:

[0056] Weigh 50 kg of dead-burned magnesia; 22.5 kg of goose warm stone; 12.5 kg of slag powder; 5.5 kg of coke powder; and 9.5 kg of bentonite by weight, wherein the ratio of the particles of the dead-burned magnesia is: 3 mm < particle size ≤ 5 mm: 1 mm < particle size ≤ 3 mm: particle size < 1 mm = 2:2:1;

[0057] The ratio of the particles of the goose warm stone is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=2:1:1;

[0058] The ratio of the slag powder particles is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=1:1.5:1;

[0059] The particle size of the coke powder is 400 mesh;

[0060] The particle size of the bentonite is 800 mesh;

[0061] The above materials were mixed and stirred for 15 minutes to obtain 100 kg of castable aggregate.

[0062] In this embodiment, the dead-burned magnesia is a dead-burned magnesia product produced by Haicheng Lier Magxita Materials Co., Ltd., whose MgO content is greater than or equal to 97%, CaO / SiO2 is not less than 2, and the bulk density is not less than 3.34 g / cm 3 , the porosity is no more than 3% and the grain boundaries are well developed.

[0063] 2) Preparation of binder

[0064] The preparation of the binder comprises the following steps:

[0065] Step 1: Weigh 0.525Kg of phenolic resin, 0.338Kg of epoxy resin, 0.263Kg of polyurethane resin, 0.098Kg of polystyrene, 0.068Kg of silicone powder, 0.068Kg of diphenyl ether, and 0.068Kg of sodium alginate according to weight, pour into a stirring tank and mix and stir for 5 minutes at room temperature;

[0066] Step 2: Weigh 0.03 kg of cobalt cyclopentaneate, pour it into a stirring tank and mix and stir for 8 minutes at room temperature;

[0067] Step 2: Finally, weigh 0.08 kg of cyclohexanone peroxide, pour it into a stirring tank, mix and stir at room temperature for 15 minutes to obtain 1.5 kg of binder.

[0068] 3) Preparation of castables:

[0069] Pour 1.5 kg of the binder prepared in step 2) into 100 kg of castable aggregate prepared in step 1), that is, the ratio of castable aggregate to binder is 100:1.5, and mix and stir for 40 minutes to obtain the castable.

[0070] [Example 3]:

[0071] A MgO-based slag stopper castable for steelmaking and tapping in a converter comprises a castable aggregate and a binder. The components of the castable aggregate are as follows by weight:

[0072] 60 parts of dead-burned magnesia; 17.5 parts of goose warm stone; 8.5 parts of slag powder; 7.5 parts of coke powder; 6.5 parts of bentonite;

[0073] The components of the binder are calculated by weight:

[0074] 45 parts of phenolic resin; 17.5 parts of epoxy resin; 12.5 parts of polyurethane resin; 6.5 parts of polystyrene; 3.5 parts of silicone powder; 3.5 parts of diphenyl ether; 4 parts of sodium alginate; 4 parts of cyclohexanone peroxide; 3.5 parts of cobalt naphthenate;

[0075] The weight percentage of the castable aggregate and the binder is 100:2.5.

[0076] The method for preparing a MgO-based slag stopper castable for steelmaking and tapping in a converter of the present embodiment comprises the following specific steps:

[0077] 1) Preparation of castable aggregate:

[0078] Weigh 60 kg of dead-burned magnesia; 17.5 kg of goose warm stone; 8.5 kg of slag powder; 7.5 kg of coke powder; and 6.5 kg of bentonite by weight, wherein the ratio of the particles of the dead-burned magnesia is: 3 mm < particle size ≤ 5 mm: 1 mm < particle size ≤ 3 mm: particle size < 1 mm = 2:2:1;

[0079] The ratio of the particles of the goose warm stone is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=2:1:1;

[0080] The ratio of the slag powder particles is: 3mm<particle size≤5mm:1mm<particle size≤3mm:particle size<1mm=1:1.5:1;

[0081] The particle size of the coke powder is 400 mesh;

[0082] The particle size of the bentonite is 800 mesh;

[0083] The above materials were mixed and stirred for 15 minutes to obtain 100 kg of castable aggregate.

[0084] In this embodiment, the dead-burned magnesia is a dead-burned magnesia product produced by Haicheng Lier Magxita Materials Co., Ltd., whose MgO content is greater than or equal to 97%, CaO / SiO2 is not less than 2, and the bulk density is not less than 3.34 g / cm 3 , the porosity is no more than 3% and the grain boundaries are well developed.

[0085] 2) Preparation of binder

[0086] The preparation of the binder comprises the following steps:

[0087] Step 1: Weigh 1.125Kg of phenolic resin, 0.438Kg of epoxy resin, 0.313Kg of polyurethane resin, 0.163Kg of polystyrene, 0.088Kg of silicone powder, 0.088Kg of diphenyl ether, and 0.100Kg of sodium alginate according to weight, pour into a stirring tank and mix and stir at room temperature for 5 minutes.

[0088] Step 2: Weigh 0.088 kg of cobalt cyclopentaneate, pour it into a stirring tank and mix and stir for 8 minutes at room temperature;

[0089] Step 2: Finally, weigh 0.100 kg of cyclohexanone peroxide, pour it into a stirring tank, mix and stir at room temperature for 15 minutes to obtain 2.5 kg of binder.

[0090] 3) Preparation of castables:

[0091] Pour 2 kg of the binder prepared in step 2) into 100 kg of castable aggregate prepared in step 1), that is, the ratio of castable aggregate to binder is 100:2.5, mix and stir for 25 minutes to obtain the castable.

[0092] The castables of each embodiment of the present invention have the advantages of high low-temperature strength and high-temperature strength, good thermal shock resistance, and short manufacturing cycle. In contrast, the amount of accelerator added in Example 2, cobalt cyclohexaneate, is smaller than that in Example 1, and the curing period for demolding at room temperature is about 25 minutes, and curing is required for about 3.5 hours after demolding; the amount of accelerator added in Example 3, cobalt cyclohexaneate, is larger than that in Example 1, and the curing period for demolding at room temperature is about 15 minutes, and curing is required for about 1.5 hours after demolding, which is significantly better than the demolding curing time of the prior art, greatly shortening the production cycle. In addition, the combined use of curing agent, cyclohexanone peroxide, and accelerator, cobalt cyclohexaneate, can make the castable quickly solidify even at room temperature (not less than 5°C) in winter.

[0093] The amount of cobalt naphthenate, the accelerator, is determined by the ambient temperature of the molding and the operating time required by the manufacturer. For example, in winter, the amount can be appropriately larger, about 4%, while in summer, about 1%.

[0094] In each embodiment of the present invention, the binder is modified by introducing polystyrene, silicone powder, diphenyl ether and sodium alginate, which can greatly improve the overall low-temperature strength and high-temperature strength of the slag stopper, improve the thermal shock resistance, and overcome the phenomenon of easy damage due to low strength during demolding, transportation, installation and delivery. In addition, the slag stopper castable of the present invention, whose aggregate main component is heavy-burned magnesia sand, has a bulk density of not less than 3.34g / cm3, and has a higher strength advantage compared with other castables with bauxite (bulk density of 2.2-2.6g / cm3) as the main component.

[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A MgO-based converter steelmaking slag plug castable, comprising a castable aggregate and a binder, characterized in that: The components of castable aggregate are calculated by weight: 50-60 parts of dead-burned magnesia; 15-25 parts of goose warm stone; 8-15 parts of slag powder; 5-10 parts of coke powder; 5-10 parts of bentonite; The components of the binder are calculated by weight: 35-45 parts of phenolic resin; Epoxy resin 15-25 parts; polyurethane resin 10-20 parts; polystyrene 5-10 parts; silicone powder 0-5 parts; diphenyl ether 0-5 parts; sodium alginate 3-5 parts; cyclohexanone peroxide 2-5 parts; cobalt naphthenate 1-5 parts; The weight percentage of the castable aggregate to the binder is 100:1.5-2.

5.

2. The MgO-based slag stopper castable for converter steelmaking and tapping according to claim 1, characterized in that: The components of castable aggregate are calculated by weight: 55 parts of dead-burned magnesia; 20 parts of goose warm stone; 10 parts of slag powder; 7.5 parts of coke powder; 7.5 parts of bentonite.

3. The MgO-based slag stopper castable for converter steelmaking and tapping according to claim 1, characterized in that: The components of the binder are calculated by weight: 40 parts of phenolic resin; 20 parts of epoxy resin; 15 parts of polyurethane resin; 7.5 parts of polystyrene; 3.5 parts of silicone powder; 3.5 parts of diphenyl ether; 4 parts of sodium alginate; 4 parts of cyclohexanone peroxide; 2.5 parts of cobalt naphthenate.

4. The MgO-based slag stopper castable for converter steelmaking and tapping according to claim 1, characterized in that: The weight percentage of the castable aggregate to the binder is 100:

2.

5. The MgO-based slag stopper castable for converter steelmaking and tapping according to claim 1, characterized in that: The dead-burned magnesia has a MgO content of greater than or equal to 97%, a CaO / SiO2 of not less than 2, and a bulk density of not less than 3.34 g / cm 3 , magnesia with a porosity of no more than 3% and well-developed grain boundaries.

Citation Information

Patent Citations

  • Low-temperature fast-curing filter material and preparation method thereof

    CN105771423A

  • Dry material for continuous casting tundish working lining, construction process and continuous casting tundish working lining

    CN112250453A